2019
DOI: 10.1177/1533033819853847
|View full text |Cite
|
Sign up to set email alerts
|

Setup Error Assessment and Correction in Planar kV Image- Versus Cone Beam CT Image-Guided Radiation Therapy: A Clinical Study of Early Breast Cancer Treated With External Beam Partial Breast Irradiation

Abstract: Objective: To compare differences in setup error assessment and correction between planar kilovolt images and cone beam computed tomography images for external beam partial breast irradiation during free breathing. Methods: Nineteen patients who received external beam partial breast irradiation after breast-conserving surgery were recruited. Interfraction setup error was acquired using planar kilovolt images and cone beam computed tomography. After online setup correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…However, VMAT-5B appeared to be more robust than VMAT-10B because slight CTV underdosage and acceptable increased dose to the OARs were noted in this group. Reportedly, couch shifts in patient setup were impossible to eliminate and the mean magnitudes were generally between 1 mm and 5 mm with imaging guidance [14][15][16]. Similar to previous data [14,16], we found ~3 mm setup errors in all directions (unpublished) in a group of patients who underwent mastectomy and immediate implant-based reconstruction using weekly cone-beam CT (CBCT).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, VMAT-5B appeared to be more robust than VMAT-10B because slight CTV underdosage and acceptable increased dose to the OARs were noted in this group. Reportedly, couch shifts in patient setup were impossible to eliminate and the mean magnitudes were generally between 1 mm and 5 mm with imaging guidance [14][15][16]. Similar to previous data [14,16], we found ~3 mm setup errors in all directions (unpublished) in a group of patients who underwent mastectomy and immediate implant-based reconstruction using weekly cone-beam CT (CBCT).…”
Section: Discussionsupporting
confidence: 81%
“…Inter-fractional patient setup errors are another source of dose variability. Generally, the errors are in the order of several millimeters when pretreatment setup verifications have been routinely performed [14][15][16]. Considering the high modulations and steep dose fall-off in VMAT, a tiny setup error of several millimeters is capable to induce significant dose loss in the target [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits of daily IGRT need to be balanced against the costs, added time, doses and institutional-based PTV margins. Additionally, our results showed that residual setup errors remain present after the daily online IGRT correction because rigid registration fails to correct target deformation and anatomical motion of normal tissues and target during treatment [35] .…”
Section: Discussionmentioning
confidence: 87%
“…These artifacts can lead to inaccurate dose calculations and impair the ability to accurately target the tumor, which can compromise the success of the radiotherapy treatment. Secondly, CBCT images have a field of view that is not typically large enough to include the entire patient’s cross-section, leading to part of the patient’s anatomy not being captured particularly if the tumour is lateralised [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%